Pendampingan Open Laboratorium untuk Pengembangan Kemampuan Bekerja Ilmiah Siswa di Sekolah Menengah Atas Islam Diponegoro - Chandra Sundaygara; Sudi Dul Aji; Adnan Nasution; Muhammad Sayyadi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2026)
Scientific work skills are used to build physics knowledge correctly and logically. which can be developed through practical activities. However, not all schools have adequate practical equipment. Observations show that SMA Islam Diponegoro still does not have a physics laboratory and experimental equipment is still limited in number and type, so practical activities are rarely carried out, which has an impact on students' scientific work skills that have not developed optimally. Therefore, community service activities were carried out in the form of Open Lab, which aims to provide students with experience in conducting practicals through concrete practical media and virtual PhET. Community service activities were carried out in the form of training and mentoring for practicals attended by 20 students. Based on the results of the scientific work ability assessment rubric, it was found that students' abilities were in the good category with an average scientific work ability score of 75.35. Indicators of scientific work ability that developed very well after the practicum were observation, implementation of the practicum, and presentation of results. However, aspects of data analysis and evaluation still need to be improved because the scores were lower than other indicators.